Strategi Promosi Penyelenggaraan Wisata Outbound Dalam Meningkatkan Kunjungan di Taman Agro Wisata Bukit Naang Kabupaten Kampar - Yanti, Risna; Febrisa, Yutia (Komunitas Manajemen Kompetitif, 2015)
Abstract: In promoting the attraction Agro Tourism Park Hill Naang as outbound tourism in Kampar, the strategy undertaken by the manager of Agro Wisata Taman Bukit Naang among others: Hold exhibitions and distribute brochures to visitors; By using print, electronic, social media and blogs; Information from mouth to mouth. There are some things that become obstacles for management Taman Bukit Naang Agro Tourism Kampar district in conducting kepromosiannya, namely: Lack of funds for promotion; The time is not right to conduct a campaign; The absence of public transport that passes through the causeway to the vehicle in Taman Bukit Naang Agro Tourism; Less passage of the campaign carried out; Not its precise target promotion undertaken. The work done by the manager of Agro Tourism Park Hill Naang in Kampar regency in mengetasi problems were found in outbound tourism in an effort to promote it, namely: Improving the service that is provided by the board and employees in Taman Bukit Naang Agro Tourism; Hold a public transport that will pass between the causeway to enter the vehicle Taman Bukit Naang Agro Tourism. Keywords: Promotion Strategy, Outbound Tourism, Agro Tourism Park Hill Naang